Character Education: The Analysis of Archival Work Experiences Using CIPP Model at UPBJJ-UT Semarang - Hascaryo Pramudibyanto; Eko Andy Purnomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The crisis is occurred in Indonesia. It is caused by the weakness of the education system that has not made thecommunity have the ability and independence, the lack of strong mental foundation development, and the weakness of competitiveness. The government has implemented the KKNI-based curriculum to strengthen the student’s compet it iveness and character. The focus of lecturing not only conveys the materials, but also there are four things: 1). attitude, 2). work ability, 3). knowledge, 4). managerial and responsibility. Through archival work experiences is expected to connect between universities, especially Open University and field employment.The demands of the field employment are not only for the theory but also the students ‘outstanding characters;such as honesty, discipline, work ethic, competitiveness, and  loyalty. Based on the observations on archival work experiences, the instruments still emphasize only the knowledge aspect which is less able to measure anddevelop the student’ characterist ics. This research was conducted at UPBJJ-UT Semarang by taking samples ofthree regencies / cities; such as Semarang, Batang, and Pati. The research uses descriptive research based onCIPP evaluation model. The CIPP model has a special component in the evaluation of context, input, process,and product. The result shows that the implementation of archival work experiences had been done well.Lecturers and advisors have built character education to students either directly or indirectly. In contrast, it hadnot been clear character assessment. Therefore, it is necessary to plan the student’ character assessmentinstrument clearly and precisely which is integrated in final assessment. The characters building that can be builtin archival work experiences are discipline, honest, creative, curiosity, passion, hard work, friendly / communicative, responsibility, and environment awareness. In conclusion, it is expected that there is an instrument of student character education assessment in archival work experiences. Keywords: character education, archival work experiences, CIPP model